Correlation of river water and local sea‐ice melting on the Laptev Sea shelf (Siberian Arctic). Issue 1 (31st January 2013) - Bauch, Dorothea; Hölemann, Jens A.; Nikulina, Anna; Wegner, Carolyn; Janout, Markus A.; Timokhov, Leonid A.; Kassens, Heidemarie
Abstract : [1] Hydrographic and stable isotope (δ 18 O) data from four summer surveys in the Laptev Sea are used to derive fractions of sea‐ice meltwater and river water. Sea‐ice meltwater fractions are found to be correlated to river water fractions. While initial heat of river discharge is too small to melt the observed 0–158 km 3 of sea‐ice meltwater, arctic rivers contain suspended particles and colored dissolved organic material that preferentially absorb solar radiation. Accordingly, heat content in surface waters is correlated to river water fractions. But in years when river water is largely absent within the surface layer, absolute heat content values increase to considerably higher values with extended exposure time to solar radiation and sensible heat. Nevertheless, no net sea‐ice melting is observed on the shelf in years when river water is largely absent within the surface layer. The total freshwater volume of the central‐eastern Laptev Sea (72–76°N, 122–140°E) varies between ~1000 and 1500 km 3 (34.92 reference salinity). It is dominated by varying river water volumes (~1300–1800 km 3 ) reduced by an about constant freshwater deficit (~350–400 km 3 ) related to sea‐ice formation. Net sea‐ice melt (~109–158 km 3 ) is only present in years with high river water budgets. Intermediate to bottom layer (>25 salinities) contain ~60% and 30% of the river budget in years with low and high river budgets, respectively. The average mean residence time of shelf waters was ~2–3 years during 2007–2009. Key points: Sea‐ice meltwater and river water fractions are correlated on Arctic shelves Heat content in surface waters is correlated to river water fractions Sea‐ice‐related freshwater deficit about constant (~350–400 km 3 ) in all years Sea‐ice melt (up to 158 km 3 ) only present in years with high river budgets